Papers on development and rural poverty - Ray, Nandita (ed.) (Anantpur. A.P., 1988)
This book brings together essays written by Young India Project activists groups over a period of six years from 1980 to 1986. In terms of themes and treatment, the essays reflect a definite change, maturity and thought over the period covered. These essays are the result of, 1) an honest evaluation of Young India Project's efforts in implementing rural development programmes and, 2) an attempt to understand the failures of those efforts and the causes of rural poverty in India. The essays also reveal the efforts made in order to understand how social formations work and how economic and political structures perpetuate poverty. They end with Young India Project's understanding of what needs to be done in India to create a just and genuine democratic society. As the editor of this collection has observed, there is an open and undogmatic approach in Young India Project's attempt to relate to socio-economic and political inequalities and the causes thereof.
Keywords: Economic development